The Drosophila KIF1A Homolog unc-104 Is Important for Site-Specific Synapse Maturation - Zhang, Yao V.; Hannan, Shabab B.; Stapper, Zeenna A.; Kern, Jeannine V.; Jahn, Thomas R.; Rasse, Tobias M. (Frontiers in Cellular Neuroscience, 2016)
Abstract Mutations in the kinesin-3 family member KIF1A have been associated with hereditary spastic paraplegia, hereditary sensory and autonomic neuropathy type 2 and intellectual disability. Both autosomal recessive and autosomal dominant forms of inheritance have been reported. Loss of KIF1A or its homolog unc-104 causes early postnatal or embryonic lethality in mice and Drosophila, respectively. In this study we use a previously described hypomorphic allele of unc-104, unc-104bris, to investigate the impact of partial loss-of-function of kinesin-3 function on active zone formation at the Drosophila neuromuscular junction. unc-104bris mutants exhibit synaptic defects where a subset of synapses at the neuromuscular junction lack the key active zone organizer protein Bruchpilot. Modulating synaptic Bruchpilot levels by ectopic overexpression or RNAi-mediated knockdown suggests that the loss of active zone components such as Ca2+ channel and Liprin-α from these synapses is caused by impaired kinesin-3 transport rather than due to the absence of Bruchpilot at these synapses. In addition to defects in active zone maturation, unc-104bris mutants display impaired transport of dense core vesicles and synaptic vesicle associated proteins, among which Rab3 has been shown to regulate the distribution of Bruchpilot to active zones. Overexpression of Rab3 partially ameliorates synaptic phenotypes of unc-104bris neuromuscular junction, suggesting that lack of presynaptic Rab3 may contribute to defects in synapse maturation.